A Review on Oral Candida as Commensal and Opportunistic Pathogen - Priyanka Debta1, Santosh Kumar Swain2, Mahesh Chandra Sahu3, Fakir Mohan Debta4, Jatindra Nath Mohan (Institute of Medico-legal Publications Pvt Ltd, 2020)
Oral candidiasis, commonly referred to as “thrush,” is an opportunistic fungal infection that commonlyaffects the oral mucosa. The various forms of oral and maxillofacial candidiasis are pseudomembranous,acute, chronic, median rhomboid glossitis, perioral dermatitis, and angular cheilitis. The main causativeagent Candida albicans, is a highly versatile commensal organism that is well adapted to its human host,continuing rise in the development of pathogenicity and resistance to traditional antifungal agents. Thusneedto develop novel therapeutic strategies that can find the early resistance to particularantifungal. So theclinician can be better able to prescribe effective antifungal for oral candidiasis.